Pengembangan Sistem Pelayanan Pengaduan Pelanggan Pada PT. PLN (Persero) Rayon Malang Kota - Wahyudin Satrio Hapsoro; Agi Putra Kharisma; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Customer responses is very important for a company.The better and faster services provided to customers, the more positive responses will be received by the company. This is called a â€œpublic goodâ€ and PLN Malang City Rayon is trying to implement it by implementing a Customer Complaint Service System at the PLN Malang City Rayon office. This Customer Complaint Service System was created to help shorten time of Malang City PLN Rayon employees in resolving complaints made by customers. The research method is by plunging directly to survey the PLN Malang City Rayon to get information about what needs are needed by the Customer Complaint Service System. Using System Development Life Cycle (SDLC) method with the identification phase, analysis phase, design phase, implementation phase and trial phase. Testing is done by survey using questionnaires to determine the level of efficiency and effectiveness of the performance of employees of PLN Malang Malang City when before and after the implementation of Customer Complaint Service Systems. So it was concluded that this customer complaint service system facilitates and helps employees to process customer complaint data more quickly, efficiently and effectively.